Effect of Annealing Temperature on the Crystallographic and Optical Properties of ZnO Films (Journal of the College of Basic Education, 2022)
ZnO Polycrystalline films were prepared on glass substrate by solvent evaporation at 25°C, and post annealed in air at range of annealing temperatures of (100, 200,300°C) for 1 hour. The samples were characterized by analyzing the structural and optical properties. X-Ray diffraction results